Inventions for Industry. Canadian Patents and Development Limited and the Commercialization of University Research in Canada - Kretz, Andrew (Scientia Canadensis, 2013)
From 1948 to 1991, Canadian Patents and Development Limited (CPDL) managed the commercialization of inventions and discoveries arising from government departments and agencies, as well as those disclosed to it by universities and others publicly funded organizations. The existence of CPDL, however, is rarely recognized in scholarship and discussions of Canadian science, technology, and innovation; its history is largely unobserved. This paper introduces a history of CPDL into the literature and contributes to a more complete understanding of the history of technology transfer in Canada. In so doing, this paper may help those interested in research commercialization understand the dynamics affecting technology transfer intermediary organizations and government policy instruments promoting the patenting and licensing of publicly funded research.